2014
DOI: 10.1074/jbc.m113.526376
|View full text |Cite
|
Sign up to set email alerts
|

The Bidirectional NiFe-hydrogenase in Synechocystis sp. PCC 6803 Is Reduced by Flavodoxin and Ferredoxin and Is Essential under Mixotrophic, Nitrate-limiting Conditions

Abstract: Background: Cyanobacterial hydrogenases are claimed to produce hydrogen via NAD(P)H, which contradicts thermodynamic considerations; the physiological function of these hydrogenases is unresolved. Results: Flavodoxin/ferredoxin reduce cyanobacterial hydrogenases, which are essential under mixotrophic, nitrate-limiting conditions. Conclusion: Cyanobacterial bidirectional hydrogenases are electron sinks for reduced flavodoxin/ferredoxin. Significance: This study provides a basis for a target-oriented enhancement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
126
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(137 citation statements)
references
References 53 publications
(46 reference statements)
4
126
0
Order By: Relevance
“…This is consistent with the strong upregulation (top 2% to 12% of most-changing transcripts observed) in the dark of the hox genes (hoxE, hoxF, hoxU, hoxY, and hoxH, which are sll1220, sll1221, sll1223, sll1224, and sll1226) that encode the bidirectional NiFe-hydrogenase, as well as hydrogenase maturation gene hypA1 (slr1675, top 1% of changing transcripts) (see also Table S4 in the supplemental material). Interestingly, the largest overall fold change was observed for sll0741, encoding the pyruvate flavodoxin/ferredoxin oxidoreductase, which was recently shown to be the electron source of the hydrogenase (37). However, protein levels of ferredoxin-nitrite reductase remained stable, whereas ferredoxin-nitrate reductase was not detected (see Table S1).…”
Section: Resultsmentioning
confidence: 90%
“…This is consistent with the strong upregulation (top 2% to 12% of most-changing transcripts observed) in the dark of the hox genes (hoxE, hoxF, hoxU, hoxY, and hoxH, which are sll1220, sll1221, sll1223, sll1224, and sll1226) that encode the bidirectional NiFe-hydrogenase, as well as hydrogenase maturation gene hypA1 (slr1675, top 1% of changing transcripts) (see also Table S4 in the supplemental material). Interestingly, the largest overall fold change was observed for sll0741, encoding the pyruvate flavodoxin/ferredoxin oxidoreductase, which was recently shown to be the electron source of the hydrogenase (37). However, protein levels of ferredoxin-nitrite reductase remained stable, whereas ferredoxin-nitrate reductase was not detected (see Table S1).…”
Section: Resultsmentioning
confidence: 90%
“…In the cyanobacterium Synechocystis spp. PCC 6803 it was shown that the bidirectional hydrogenase could also directly accept electrons from Fd or flavodoxin, which explains the production of H 2 by overreduction of the Fd pool in the light or fermentative metabolism under anoxic dark conditions [91].…”
Section: Group 3d This Subgroup Consists Of Bidirectional Heteromultmentioning
confidence: 99%
“…Cyanobacterial hydrogenases, thus, are linked to both photosynthetic and respiratory electron transport chains (Cournac et al 2004;Schmitz and Bothe 1996;Appel and Schulz 1996). Moreover, recent evident suggests that both ferredoxins and flavodoxins could act as electron donors to the cyanobacterial hydrogenase (Gutekunst et al 2014). Besides the major enzymatic differences between [FeFe] and [NiFe]-enzymes described above, it must be noted that [NiFe]-hydrogenases are constitutively expressed, while the expression of [FeFe]-hydrogenases requires anaerobic induction.…”
Section: Hydrogenasesmentioning
confidence: 96%